Pertussis. (December 2021) - Galiza, Eva P; Calvert, Anna; Drysdale, Simon B; Heath, Paul T
Abstract: Pertussis is an infectious disease of the respiratory tract caused by the Gram-negative bacterium Bordetella pertussis . Pertussis vaccines have led to a significant reduction in the incidence and severity of pertussis in infants worldwide. Despite this decrease in incidence, pertussis remains one of the principal causes of vaccine-preventable death; the World Health Organization reported an estimated 24.1 million cases and 160, 700 paediatric deaths in 2014. Pertussis infection can occur at any age. In the last 20 years, there has been an increase in the number of adolescent and adult cases reported in high-income countries, including those with high vaccination coverage. These cases represent a potential source of infection for unimmunized infants, who typically have a more severe course with higher mortality. Pertussis infection in previously immunized adults, elderly individuals or young infants frequently presents with atypical symptoms and can easily be overlooked as a diagnosis. This review provides a summary of Bordetella pertussis and discusses diagnostic tests, treatment and prevention.